Europejskie standardy usług publicznych (zarys wybranych problemów) - Kowalczyk, Lucjan (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The presentation describes European standards of public services, interpreted as a set of regulations included in the sources of primary and secondary European law that refer to administration, law enforcement, social services and utilities. Those groups are further subdivided into specialised services. The presentation attempts to identify European regulations oriented towards specialised public services, at the same time taking into account the approach employed in the Programme for Institution Building. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 606-622